Milia En Plaque-An Unusual Presentation - Mendiratta Vibhu; Sarkar Rashmi; Sharma R. C; Koranne R. V (Wolters Kluwer Medknow Publications, 1999)
Milia en plaque, an unusual clinical variant of milia, has been reported mainly in the post-auricular area. We report a case of milia en plaque over an unusual site i.e. over the angle of the mouth present over lesions of pityriasis alba.